Conversational Implicature in the Food Product Advertisement: There is Taste, There is Price - Sari, Putri Ardina Setia; Rosita, Farida Yufarlina; Pancarrani, Berlian (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
This study explores the use of conversational implicature in the